Reducing Energy Consumption in the Synthesis of Dimethyl Ether (DME) from Methanol Dehydration by Modifying Heat Transfer Unit Using Aspen HYSYS - Faisal, Muhammad Auliya; Puspaningrum, Faradiba; Novalia, Fera Yeniza; Sabrilla, Tian Shilfa (UPT Laboratorium Terpadu, Universitas Diponegoro, 2024)
In the pursuit of a transport sector free from fossil fuels, the incorporation of Dimethyl ether (DME) emerges as a commendable ecological substitute. The DME is a synthetically produced serves as a viable alternative to conventional fuels such as diesel and liquified petroleum gas (LPG). The Dimethyl Ether (DME) production is carried out by catalytic dehydration of methanol over an acidic zeolite-based catalyst. The technological process for the DME synthesis was simulated using Aspen HYSYS based on the combined operating parameters of the reaction dynamic model for the methanol dehydration reaction. This paper attempts to evaluate a modification in dehydration of methanol process to reducing energy consumption by modifying heat transfer unit. The heater and cooler heat transfer units were converted into heat exchangers (HE) by utilizing the output of the process that can be used for other processes so that energy consumption is reduced. The temperature of reaction and the heat transfer unit are modified to reduce energy consumption from 11.850 MMBtu/h to 7.6291 MMBtu/h by changing one heater and one cooler with two heat exchangers. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).